Utilizing Monocarboxylate Transporter 1-Mediated Blood–Brain Barrier Penetration for Glioblastoma Positron Emission Tomography Imaging with 6-[18F]Fluoronicotinic Acid - Dillemuth, Pyry; Ayo, Abiodun; Airenne, Tomi T.; Lövdahl, Petter; Bakay, Emel; Zhuang, Xiaoqing; Liljenbäck, Heidi; Paunonen, Sami Tuomas; Kunnas, Jonne; Filppu, Pauliina; Rajander, Johan; Johnson, Mark S.; et al. (American Chemical Society (ACS), 2025)
Glioblastoma is the most malignant brain tumor in adults, and its prognosis remains dismal. The blood–brain barrier impedes the effectiveness of many drugs, which are otherwise effective for cancer treatment. Monocarboxylate transporter 1 (MCT1) is expressed on endothelial and glioblastoma cells. Our approach aims to leverage MCT1 to transport theranostic agents across the blood–brain barrier. In this context, we present herein the application of fluorine-18-labeled nicotinic acid (denoted as [18F]FNA) for glioblastoma imaging using positron emission tomography (PET). An intracranial mouse model of human glioblastoma was prepared by using patient-derived BT12 cells. PET imaging, ex vivo biodistribution, brain tissue autoradiography, and tumor and tissue uptake kinetic analyses were performed. Additionally, the ligand–target interaction was studied using in silico modeling. The xenografted glioblastomas were distinctly visualized in all 18 mice with a mean standardized uptake value of 0.92 ± 0.11 and tumor-to-brain ratio of 1.66 ± 0.17. The tumor uptake of intravenously administered [18F]FNA decreased by 76% on average when MCT1 was inhibited, whereas preadministration of 60 mg/kg niacin significantly enhanced [18F]FNA tumor uptake. The G protein-coupled receptor GPR109A is a high-affinity receptor for niacin (nicotinic acid). In silico simulations indicated that both niacin and fluorinated nicotinic acid (FNA) interact with the GPR109A receptor in a similar manner. In the presence of a GPR109A inhibitor in in vivo experiments, the tumor residence of [18F]FNA was extended. [18F]FNA has demonstrated its potential for PET imaging in a clinically relevant orthotopic glioblastoma model, and MCT1 plays a crucial role in [18F]FNA transport. The results pave the way for the development of niacin-derived theranostics for glioblastoma care.